Addition of the Lewis Acid Zn(C6F5)2 Enables Organic Transistors with a Maximum Hole Mobility in Excess of 20 cm2 V−1 s−1. Issue 27 (10th May 2019) - Paterson, Alexandra F.; Tsetseris, Leonidas; Li, Ruipeng; Basu, Aniruddha; Faber, Hendrik; Emwas, Abdul‐Hamid; Panidi, Julianna; Fei, Zhuping; Niazi, Muhammad R.; Anjum, Dalaver H.; Heeney, Martin; Anthopoulos, Thomas D.
Abstract: Incorporating the molecular organic Lewis acid tris(pentafluorophenyl)borane [B(C6 F5 )3 ] into organic semiconductors has shown remarkable promise in recent years for controlling the operating characteristics and performance of various opto/electronic devices, including, light‐emitting diodes, solar cells, and organic thin‐film transistors (OTFTs). Despite the demonstrated potential, however, to date most of the work has been limited to B(C6 F5 )3 with the latter serving as the prototypical air‐stable molecular Lewis acid system. Herein, the use of bis(pentafluorophenyl)zinc [Zn(C6 F5 )2 ] is reported as an alternative Lewis acid additive in high‐hole‐mobility OTFTs based on small‐molecule:polymer blends comprising 2, 7‐dioctyl[1]benzothieno [3, 2‐b][1]benzothiophene and indacenodithiophene–benzothiadiazole. Systematic analysis of the materials and device characteristics supports the hypothesis that Zn(C6 F5 )2 acts simultaneously as a p ‐dopant and a microstructure modifier. It is proposed that it is the combination of these synergistic effects that leads to OTFTs with a maximum hole mobility value of 21.5 cm 2 V −1 s −1 . The work not only highlights Zn(C6 F5 )2 as a promising new additive for next‐generation optoelectronic devices, but also opens up new avenues in the search for high‐mobility organic semiconductors. Abstract : Incorporation of the molecular Lewis acid bis(pentafluorophenyl)zinc [Zn(C6 F5 )2 ] into a high‐hole‐mobility organic small‐molecule/polymer blend yields transistors with a maximum mobility of 21.5 cm 2 V −1 s −1 . Analysis of the materials and devices reveals that Zn(C6 F5 )2 acts as a simultaneous p‐dopant and microstructure modifier. Density functional theory calculations predict that the formation of molecular complexes mediates these synergistic effects.